2005
DOI: 10.1097/01.mao.0000169794.76072.16
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Continuous Interleaved Sampling and Simultaneous Analog Stimulation Speech Processing Strategies in Newly Implanted Adults with a Clarion 1.2 Cochlear Implant

Abstract: This study demonstrates that important learning occurs during the first several weeks of cochlear implant use, making it difficult to adequately compare performance with different speech processing strategies. However, the finding that patients often prefer the strategy they understand speech the best with supports the clinical practice of letting adult patients select their preferred strategy without formally evaluating speech perception with each available strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…On the CNC word recognition task, the scores ranged from 0% to 68%, where chance performance would yield a score near 0% since this is an open-set task. This range of performance on the CNC task is consistent with previous studies that tested listeners with earlier generation CI devices similar to those tested in the present study (Waltzman, Cohen, and Roland, 1999; Zwolan et al, 2005), but lower on average than CNC scores obtained with more recent devices (Balkany et al, 2007; Fitzgerald et al, 2007; Koch, Osberger, Segel, and Kessler, 2004; Skinner et al, 2006). Note that the group of seven CI users with poor cumulative d' scores had CNC word identification scores of 0% to 30%, whereas the four CI users whose cumulative d' scores were within the normal-hearing range had CNC word scores of 46% to 68%.…”
Section: Resultssupporting
confidence: 92%
“…On the CNC word recognition task, the scores ranged from 0% to 68%, where chance performance would yield a score near 0% since this is an open-set task. This range of performance on the CNC task is consistent with previous studies that tested listeners with earlier generation CI devices similar to those tested in the present study (Waltzman, Cohen, and Roland, 1999; Zwolan et al, 2005), but lower on average than CNC scores obtained with more recent devices (Balkany et al, 2007; Fitzgerald et al, 2007; Koch, Osberger, Segel, and Kessler, 2004; Skinner et al, 2006). Note that the group of seven CI users with poor cumulative d' scores had CNC word identification scores of 0% to 30%, whereas the four CI users whose cumulative d' scores were within the normal-hearing range had CNC word scores of 46% to 68%.…”
Section: Resultssupporting
confidence: 92%
“…Similarly, another multicenter study with 51 participants found that 41% preferred analog stimulation (Koch, Osberger, Segel, & Kessler, 2004). In both studies, there may have been an effect of unequal exposure to the strategies, but a wellcontrolled crossover trial by Zwolan et al (2005) with 25 participants still found that a notable proportion (16%) preferred analog stimulation at the end of the 6-month evaluation-with those preferring analog showing a very strong preference to it. Participants tended to perform best with the strategy they preferred.…”
Section: Introductionmentioning
confidence: 98%
“…These implants are driven by previousgeneration processors including the Platinum Sound TM Processor (PSP), Platinum behind-the-ear (BTE) Processor, Clarion S-Series, Clarion 1.2, and Clarion 1.0. These processors supported the continuous interleaved sampling (CIS) (Wilson et al, 1993;Zwolan et al, 2005), simultaneous analogue stimulation (SAS) (Zwolan et al, 2005;Zimmerman-Phillips and Murad., 1999;Osberger and Fisher 1999), and multiple/paired pulsatile stimulation (MPS/PPS) sound coding strategies (Zwolan et al, 2005). SAS provides simultaneous stimulation to all electrodes using bipolar electrode coupling in which each electrode is paired with another electrode that is in close proximity, while CIS provides non-simultaneous pulsatile stimulation using monopolar coupling.…”
Section: Introductionmentioning
confidence: 99%